Psychological and Physical Readiness Profiles for Return to Sport in Patients After Anterior Cruciate Ligament Reconstruction: An Analysis of 822 Patients. - Marmura, Hana; Spang, Jeffrey; Baez, Shelby E.; Roman, Dylan P.; Ulman, Sophia; Butler, Lauren; Walker, Cody; Douthit, Taylor; Kuenze, Christopher M.; Prati, Victor V.; Sachleben, Brant; Phan, Lucy; et al. (Orthopaedic Journal of Sports Medicine, 2026)
Background: Psychological factors influence return to sport (RTS) and reinjury rates following anterior cruciate ligament (ACL) reconstruction (ACLR). However, many RTS decisions are made without considering psychological factors, or consider psychological and physical factors in isolation, leading to suboptimal RTS and reinjury rates. Purpose: To identify distinct profiles of psychological and physical readiness to RTS following ACLR using strength- and performance-based measures of physical readiness and to examine the extent to which these readiness domains align. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Data from the ACL Reconstruction Rehabilitation Outcomes Workgroup (ARROW) registry were used to construct patient profiles of psychological and physical readiness to RTS based on established criteria. Psychological readiness was defined by an ACL Return to Sport after Injury Scale (ACL-RSI) score ≥65 points out of 100. Strength-based and performance-based physical readiness was defined by a limb symmetry index ≥90% in isokinetic quadriceps strength and single-limb hop testing, respectively. Frequencies of all profiles were reported, alignment between psychological and physical domains was assessed, and sensitivity analyses were conducted to investigate differences in age, sex, and time since surgery. Results: A total of 822 patients were included in the analysis (age: mean ± SD, 18.8 ± 6.2 years; 51% female). The most common profile represented patients who met psychological (ACL-RSI) and performance-based physical readiness criteria (single-leg hop) but not strength-based physical readiness criteria (quadriceps strength) (32%; 261/822). When considering ACL-RSI, single-leg hop, and quadriceps criteria together, psychological and physical readiness did not align for 69% (571/822) of patients. Patients in the "neither psychologically nor physically ready" profile were older than patients in any other profiles. Male patients obtained psychological and physical readiness scores that aligned more often than female patients. Conclusion: There were a variety of distinct profiles of psychological and physical readiness in patients post-ACLR. Psychological, strength-based, and performance-based physical readiness to RTS criteria aligned for less than one-third of participants. Patients who did not meet psychological or physical readiness criteria tended to be older in age, and male patients were more likely to have alignment between their psychological and physical readiness domains.